High ambient temperatures associations with children and young adult injury emergency department visits in NYC - Blean Girma; Bian Liu; Leah H Schinasi; Jane E Clougherty; Perry E Sheffield (IOP Publishing, 2023)
Injury is a significant health burden for children and young adult and may be an increasing concern in a warming climate. Research reveals many impacts to children's health associated with hot weather and heatwave events, including a growing literature on the association between high ambient temperature and injury, which may vary by intent such as injury resulting from violence. However, little is known about how this association varies across different types of injury and subgroups of young people. We examined relationships between warm season ambient temperature and intentional and unintentional injury among children and young adults in New York City (NYC). Within a case-crossover design, our study observed injury-related emergency department (ED) visits from the New York Statewide Planning and Research Cooperative System administrative dataset. Injuries were categorized as unintentional or intentional injuries during the warm season (May through September) in NYC from 2005 to 2011 among patients (0, 1-4, 5-9, 10-14, 15-19, 20-25 years old (y.o.)). Conditional logistic regression models with distributed lag non-linear functions were used to model the cumulative odds ratio (OR) injury-related ED visit over 0-5 lag days. Analyses were stratified by age group and sex to understand how associations vary across young people of different age and sex. There were a total of 572 535 injury-related ED visits. The largest effect of elevated temperature (daily minimum 77°F vs 48°F) was for unintentional injury among 5-9 y.o. (OR 1.32, 95% CI 1.23, 1.42) and for intentional injury among 20-25 y.o. (OR 1.54, 95% CI 1.28, 1.85). Further stratified analyses revealed that the highest risk of unintentional injury was among 5-9 y.o. males and 20-25 y.o. males for intentional injury. Our results suggest that high ambient temperatures are associated with higher odds of unintentional and intentional injuries among children. This work adds to a growing body of literature demonstrating the adverse impacts of heat on children, and suggests the need for messaging to parents and children about adopting adaptive strategies to prevent injuries when it is hot outside.